Design, synthesis, biological evaluation, and in silico studies of 2‐aminobenzothiazole derivatives as potent PI3Kα inhibitors. Issue 10 (3rd June 2022) - Haider, Kashif; Ahmad, Kamal; Najmi, Abul Kalam; Das, Subham; Joseph, Alex; Shahar Yar, M.
Abstract: A new series of 2‐aminobenzothiazole derivatives was designed, synthesized and evaluated for their anticancer activity against the MCF7, MDAMB‐231, and HepG2 cancer cell lines. All synthesized derivatives (8a–8n ) demonstrated moderate to high anticancer activity against the tested cell lines. As the most potent compound in the series, compound 8i displayed excellent inhibitory potency with an IC50 value of 6.34 μM and compound 8m displayed an IC50 value of 8.30 µM against the MCF7 cell line compared to the standard drug HS‐173 (IC50  = 10.25 μM). PI3K enzyme activity assays demonstrated that compound 8i is highly selective against PI3Kα, with an IC50 value of 1.03 nM. Wound healing assays and cell cycle analysis of compounds 8i and 8m revealed that both compounds suppressed the migration of MCF7 cells and induce cell cycle arrest in the S phase. In the cell death assay, compound 8i was revealed to induce apoptosis in a dose‐dependent pattern; further Western blot assays revealed that compound 8i obviously decreases the levels of the antiapoptotic proteins Bcl‐xL and Mcl‐1. Downregulation of the expression of p‐Akt confirmed the PI3K inhibitory activity of compound 8i . The molecular docking and molecular dynamics simulation studies performed were found in agreement with the PI3Kα inhibitory activity assessments performed experimentally. Abstract : New 2‐aminobenzothiazole derivatives were designed, synthesized, and evaluated for their activity against three cancer cell lines. All synthesized derivatives (8a–8n ) demonstrated moderate to high anticancer activity against the tested cell lines. Compound 8i was revealed to induce apoptosis in a dose‐dependent pattern, likely by decreasing the levels of the antiapoptotic proteins Bcl‐xL and Mcl‐1. Downregulation of p‐Akt expression confirmed the PI3K inhibitory activity of compound 8i .